การเพาะเลี้ยงสาหร่ายไก (cladophora และ microspora) เพื่อเป็นอาหารเสริมในการเลี้ยงปลานิล - ศุภรัตน์ มะโน (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The effect of mass culture of the edible freshwater Kai algae, Cladophora and Microspora, cultured in cement raceway pondsusing fermented soybean cake water supplemented with Dipotassium hydrogen ortho phosphate (K2HPO4) 0, 20, 25 and 30mgL-1 and harvest Kai algae from each sample compounded with Nile Tilapia fishfood 5% by weight to feed forNile Tilapia fish juvenile. Concentrate on Growth rate, Nutrient, Carotenoid quantitative and water quality during culture. The resultsshowed thatKai algae, culturedwith Dipotassium hydrogen ortho phosphate30 mgL-1produced the highest value of growth rate of yield 65.35 gm-2 (fresh weight) , The highest value of carotenoid and protein of Kai algae were 1118.75 µgg-1 (dry weight) and 15.05% respectively, which were statistically significant different (p<0.05) higher than other treatment groups.The highest value of protein were 15.05% respectively, which were statistically significant different (p<0.05) higher than other treatment groups.The water quality during the cultivation of Kai algae showed that the highest air temperature 36.71 0Cand pH 7.80were statistically significant different (p<0.05), the highest water temperature 30.140C and the water current velocity 0.19 ms-1 were not statistically significant (p>0.05) Nile Tilapia fish food compounded with Kai algae culturedwith Dipotassium hydrogen ortho phosphate, The highest value of carotenoid were 75.00 µgg-1 (dry weight), not statistically significant different (p<0.05), highest value of protein were 26.75 % respectively, statistically significant different (p<0.05).Nile Tilapia fish, feed by food compounded with Kai algae culturedwith Dipotassium hydrogen ortho phosphate 25 mgL-1 produced the highest value of growth rate and produce 1.33 g of juvenile (average weight),analyses of the growth rate showed that the highest specific growth rate 3.63% per day and 100%survive rate were not statistically significant different (p<0.05), the highest Feed conversion ratio and Nile Tilapia fish juvenile were 1.02, which were statistically significant different (p<0.05). The highest protein of Nile Tilapia fish juvenile were 32.13% respectively, which were statistically significant different (p<0.05) This research also indicated that Dipotassium hydrogen ortho phosphateenhanced the production of growth rate, carotenoid and protein of algae. The Nile Tilapia fish food compounded withKai algae, culturedwith high concentrate of Dipotassium hydrogen ortho phosphate increase protein and tendency to produce carotenoid. The juvenile feed with integrated food had an effect on Feed conversion ratio,but had no effect to growth rate, specific growth rate and survive rate.